Literature-based character education: building character values through bahasa indonesia keilmuan (BIK) in higher education - Cahyadi, Robby (2023)
Character education in the context of higher education is one of the things that is increasingly important in developing student ethics and morals. This is done with the aim of making students become individuals with high integrity and ethics. This research examines the application of character education through the Bahasa Indonesia Keilmuan (BIK) in higher education, focusing on character values that appear in a literary work. The problems studied are: (1) the effective implementation of character education in project-based BIK learning in higher education and (2) the improvement of critical thinking skills in character education based on literary writing in higher education. Literary cases and real-life contexts are used as tools to explore character values. The research method uses descriptive qualitative and the research approach uses a value-based learning approach. In Bahasa Indonesia Keilmuan (BIK), it can be applied to texts that contain moral message content and encourage discussion about character values. In addition, the use of technology and project-based learning can enrich learning by providing opportunities for students to apply character values in relevant contexts. The results of the study show that the use of this method can effectively facilitate a deeper understanding of character, ethics, and values in the context of Indonesian language. It is hoped that through the application of character values to Indonesian language learning in higher education has significant potential to form individuals who are more aware of ethics, improve critical analysis skills, application in real life, contribute positively to society, form moral leaders, have high integrity, and as an enrichment of Indonesian language learning. By implementing all of these things, it can show a commitment to the development of student character not only in academic aspects, but also in solid character and morals.